HISTORY OF CONSTRUCTION OF HYDRAULIC STRUCTURES AND GENERAL CONCEPTS ABOUT HYDRAULIC STRUCTURES - Dildora Bahodirovna Salimov (Scholar Express Journals, 2024)
Our article entitled “A Brief History of the Construction of Hydraulic Structures and General Concepts about Hydraulic Structures” contains historical information about canals located in the geographical areas of Central Asia, their water sources, as well as scientific facts about water supply technology. Storage in these canals, as well as the basics and concepts of the construction of hydraulic structures
Keywords: Construction of hydraulic structures; geographical location of Central Asia; Dargom Canal